Terminological ambiguities in the area of postal services with a special focus on the CEP industry - Grgurović Biljana P.; Milutinović Jelena K. (Tehnika, 2021)
The paper addresses the problem of understanding and interpreting professional terminology in the field of postal services (with a special focus on the CEP industry) which abounds in specific words and phrases that are sometimes difficult to pinpoint in terms of meaning or difference between them. The paper is mainly based on relevant bibliography, rulebooks, and professional debates in which the authors have participated or which they have observed. The main emphasis is put not only on the meaning of terms, but on the importance of the context in which they are used. The findings should help all interested parties: both employees in the field and young people studying to become professionals in this sector, as well as users of postal services. Since professionals in this area, and especially those in educational institutions, explain and approach certain terminology differently, the paper points out the necessity of interpreting in accordance with theoretical framework and the context of a specific term. This approach could result in higher precision and unambiguity in interpreting, explaining, and comparing different events in the postal sector. Keeping in mind that there are no previously published papers or studies tackling this problem, the idea of the authors was to identify and explain in detail some of the most commonly used terms with varied interpretations which describe services, the market, technology known as postal, whether that is entirely correct or not.